Bendi Transportasi Tradisional di Kota Padang 1960-2019 - Rahma Yani; Zul Asri (Jurusan Sejarah FIS UNP, 2020)
This study discusses the transportation of hansom in the city of Padang because until now the hams can still survive in the city of Padang in competition with motorized vehicles. The purpose of this study is to describe the development of the dam as a traditional transportation in the progress of motorized transportation in the city of Padang from 1960-2019. Analyzing the economic life of the coachman of the city of Padang 1960-2019. The research methods used are library studies, archival studies, and interviews. The development of the hansom from 19601990 experienced competition with motorized vehicles such as oplets, bemos and city buses which were faster to the destination. Bendi in 1991-2000 experienced a decrease in passengers bdue to competing with taxis faster motorbike taxis added to the monetary crisis caused the driver of the bendi coach revenue to decrease. In 2001-2019 the bendi also experienced competition with motorized pedicabs, motorcycle taxi bases, puclic transportation, Trans Padang and online transportation. The route taken by the Andalas Plaza bendi-Muaro Lasak Beach –Purus Beach, Pasar Raya- Muaro Lasak Beach, Tanah Kongsi Market-Resident’s house, Siti Nurbaya Bridge.This gets the attentition of the adang city government on the continuity of the bendi to survive in the city of Padang by means of the coachman of the dam joined in the Empowerment of TourismConscious Groups as a supporter of tourism tourism in the city of Padang.